2011
DOI: 10.1053/j.gastro.2010.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Steatosis Progression in Adults Coinfected With HIV and Hepatitis C Virus

Abstract: Background and Aims-Hepatic steatosis is a common histological finding in patients that are co-infected with HIV and hepatitis C virus (HCV), although little is known about its natural history. We prospectively examined the natural history of steatosis in patients co-infected with HIV and HCV that attended an urban HIV clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 32 publications
(59 reference statements)
5
48
7
Order By: Relevance
“…Several studies sought to investigate the role of ART in the pathogenesis of hepatic steatosis in HIC/ HCV-coinfected populations. A recent prospective longitudinal study using paired liver biopsy data found longer ART exposure and higher CD4 levels to be protective against steatosis [50 ]. In contrast, a metaanalysis including 12 studies on risk factors for hepatic steatosis in HIV/HCV-coinfected patients could not demonstrate an effect of ART, CD4 cell counts, and HIV load, on hepatic steatosis.…”
Section: Indirect Effects Of Antiretroviral Therapy In Hiv/hepatitis mentioning
confidence: 90%
“…Several studies sought to investigate the role of ART in the pathogenesis of hepatic steatosis in HIC/ HCV-coinfected populations. A recent prospective longitudinal study using paired liver biopsy data found longer ART exposure and higher CD4 levels to be protective against steatosis [50 ]. In contrast, a metaanalysis including 12 studies on risk factors for hepatic steatosis in HIV/HCV-coinfected patients could not demonstrate an effect of ART, CD4 cell counts, and HIV load, on hepatic steatosis.…”
Section: Indirect Effects Of Antiretroviral Therapy In Hiv/hepatitis mentioning
confidence: 90%
“…The answer is ‘yes’. Generalised estimating equations,19 for instance, is an example of a tool used to account for this type of correlated data and the reader is encouraged to apply it to correlated data and multivariate analyses 20 21. It is not, however, the only alternative, as other regression techniques adjusted for cluster effect have been developed 22…”
Section: What Is the Type Of Outcome Variable And What Is The Most Apmentioning
confidence: 99%
“…The possible role of antiretroviral drugs and of HCV coinfection in the development and progression of FLD has been studied with contradictory results [12][13][14][15][16][17]. In a recent study, the BMI was found to be the major factor associated with FLD in HIV-infected patients [1].…”
Section: Introductionmentioning
confidence: 99%